DIRECTED–PROJECT BASED LEARNING AS LANGUAGE LEARNING MODEL: DESIGNING, DEVELOPING AND FIELD TESTING - Tri Pratiwi; Sufyarma Marsidin; Hermawati Syarif; Yahya Yahya (EduLite: Journal of English Education, Literature and Culture, 2018)
The aim of the present study is developing English learning model to increase students’ language skills in English subject for VIII graders of SMP N 1 Uram Jaya through Directed-Project Based Learning (DPjBL) implementation. This study is designed in Research and Development (R & D) using ADDIE model development. The researcher collected the data through the test, questionnaire, observation, and interview which were then analyzed qualitatively and quantitatively. The study revealed that Directed-Project Based Learning (DPjBL) implementation is significantly able to be one learning model allowing to increase student’s language skills.